PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN LISTING DI BURSA EFEK INDONESIA TAHUN 2016 – 2021: THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER AND NET PROFIT MARGIN ON PROFIT GROWTH IN FOOD AND BEVERAGE COMPANY LISTINGS ON THE INDONESIA STOCK EXCHANGE, 2016 – 2021 - Rouli Sukarni Situmeang; Paul Edward Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
The purpose of this study is to analyze the effect of current ratio, debt to equity ratio, total asset turnover and net profit margin on profit growth in food and beverage companies listed on the Indonesian stock exchange in 2016 – 2021. The collection of sample data in this study used the purposive sampling method with the help of SPSS software to test statistical analysis and samples used by as many as 15 food and beverage companies. Data analysis using descriptive statistics, model coefficient of determination, coefficient of multiple linear regression analysis, hypothesis test, and classical assumption test using SPSS software version 22. This study obtained a result, which shows that the current ratio, debt to equity ratio, total asset turnover and net profit margin have an effect on profit growth.